Mutations in PLOD2 cause autosomal-recessive connective tissue disorders within the Bruck syndrome-Osteogenesis imperfecta phenotypic spectrum - Puig-Hervás, M.; Temtamy, S.; Aglan, M.; Valencia, M.; Martínez-Glez, V.; Ballesta-Martínez, M.; López-González, V.; Ashour, A.; Amr, K.; Pulido, V.; Guillén-Navarro, E.; Lapunzina, P.; et al. (John Wiley & Sons, Inc., 2012)
PLOD2 and FKBP10 are genes mutated in Bruck syndrome (BS), a condition resembling osteogenesis imperfecta (OI), but that is also typically associated with congenital joint contractures. Herein, we sought mutations in six consanguineous BS families and detected changes in either PLOD2 or FKBP10 in all cases. Two probands were found with a homozygous frameshift mutation in the alternative exon 13a of PLOD2, indicating that specific inactivation of the longer protein isoform encoded by this gene is sufficient to cause BS. In addition, by homozygosity mapping, followed by a candidate gene approach, we identified a homozygous donor splice site mutation in PLOD2 in a patient with autosomal-recessive OI (AR-OI). Screening of additional samples also revealed compound heterozygous mutations in PLOD2 in two brothers, one affected with mild AR-OI and the other with mild BS. Thus, PLOD2 in addition to causing BS is also associated with AR-OI phenotypes of variable severity. © 2012 Wiley Periodicals, Inc.